Sejarah, Aplikasi dan Kritik Pragmatisme di Indonesia - Hidayat, Amirul; Herwina (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The philosophy of pragmatism has had a positive impact on the world of education in Indonesia, the early history of pragmatism has made us rich in diverse viewpoints, the philosophy of pragmatism was born amidst the onslaught of materialistic and idealist philosophies, the history and development of the philosophy of pragmatism has begun to give birth to great figures making this school survive in all areas of this aspect of life, we can find education based on pragmatism in vocational high schools and Islamic-based schools, experience-based practices and values ​​enrich learning methodology, this article is based on library study methodology which will focus to the literature review, thus enriching the reader's treasures in looking for initial references regarding the Pragmatic school in the field of education.